2000
DOI: 10.1021/bi001502s
|View full text |Cite
|
Sign up to set email alerts
|

The Skeletal Muscle Ryanodine Receptor Identified as a Molecular Target of [3H]Azidodantrolene by Photoaffinity Labeling

Abstract: Dantrolene is a skeletal muscle relaxant which acts by inhibiting intracellular Ca(2+) release from sarcoplasmic reticulum (SR). It is used primarily in the treatment of malignant hyperthermia (MH), a pharmacogenetic sensitivity to volatile anesthetics resulting in massive intracellular Ca(2+) release. Determination of the site and mechanism of action of dantrolene should contribute to the understanding of the regulation of intracellular Ca(2+) release in skeletal muscle. Photoaffinity labeling of porcine SR w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
51
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 58 publications
(115 reference statements)
3
51
0
Order By: Relevance
“…Functional studies on muscle fibers suggested the RyR as the potential target for the action of dantrolene (25,26), and respective binding sites were mapped to the protein (27)(28)(29). However, no action of dantrolene was found in most studies on single RyRs incorporated into lipid bilayers (26,30,31).…”
mentioning
confidence: 99%
“…Functional studies on muscle fibers suggested the RyR as the potential target for the action of dantrolene (25,26), and respective binding sites were mapped to the protein (27)(28)(29). However, no action of dantrolene was found in most studies on single RyRs incorporated into lipid bilayers (26,30,31).…”
mentioning
confidence: 99%
“…[ 3 H]Azidodantrolene specifically photolabels the N-terminal 1400-amino acid fragment of RyR1 cleaved by an endogenous, SR membrane-bound calpain (33) and is localized within sequence Leu 590 -Cys 609 based on the following evidence. 1) Of several synthetic RyR1 domain peptides examined, [ 3 H]azidodantrolene specifically photolabels only peptides containing the Leu 590 -Cys 609 sequence (named DP1 for domain peptide-1), and 2) an anti-RyR1 monoclonal antibody recognizing DP1 inhibits [ 3 H]azidodantrolene photolabeling of RyR1 (34).…”
mentioning
confidence: 99%
“…Recently, we have demonstrated that [ 3 H]azidodantrolene, a pharmacologically active, photoaffinity analog of dantrolene, specifically labels the N-terminal, 1400-amino acid residue fragment of RyR1 cleaved by n-calpain, a tissue-specific isoform of this Ca 2ϩ -and thiol-activated protease (13). Several studies have demonstrated that this portion of the RyR plays a significant role in the regulation of channel function (14 -18).…”
mentioning
confidence: 99%
“…A monoclonal anti-RyR1 antibody raised against rabbit terminal cisternae (25) that recognizes both the intact rabbit RyR1 and the 172 kDa, n-calpain-cleaved, N-terminal fragment of this channel (13) (26), and the specific activity was determined to be 28 Ci/mmol.…”
mentioning
confidence: 99%
See 1 more Smart Citation